Smoking Cessation Awareness Among Active and Passive Smokers in Surabaya - Guasin, Nurshafiqah; Hasanuddin, Nur Hafifah; Md Noor, Nurul Fathin Athirah; Mohd Idrus, Sharifah Nurul Fatin Afiqah; Ahmad Sufie, Muhammad Luqman Nurhakim; Nafiisa Aaliyah Fathar; Elida Zairina (Jurnal Farmasi Komunitas, 2024)
Tobacco consumption is still relatively high and increasing compared to the results of 2007 and 2013. The burden of disease in Indonesia is increasing every year, and smoking is one of the leading causes. The critical issue that has to be addressed is a lack of smoking cessation awareness among active and passive smokers. The prolonged use of tobacco products and the exposure of non-smokers to dangerous secondhand smoke both occur as the consequences of this ignorance. This study aimed to assess the willingness to quit smoking and the awareness of existing Nicotine Replacement Therapy (NRT) or QUITLINE Program. The subjects were chosen by convenient sampling for those who met the inclusion criteria, including Surabaya citizens aged 18 years and above, active smokers and passive smokers due to living/staying with active smokers. The data were collected using a self-administered questionnaire. The data were analyzed descriptively using IBM SPSS software version 26.0. About 106 subjects participated in the study consists of 77% male, 23% female, with ages ranging from 19 to 62 years. The data showed that 57.55% (n=61) of smokers, 42.45% (n=45) non-smokers.  Of 106 respondents, 67 (63.2%) had never heard about Nicotine Replacement Therapy (NRT) and 98.4% (60 smokers) had never heard of QUITLINE Program. Encouragingly, 63.9% (39 smokers) of the smokers were aware of the dangers of smoking. From this study, it can be concluded that the awareness of smoking cessation among the residents in Mulyorejo, Surabaya, was high. However, some of them were not convinced yet to stop smoking because their intention to quit smoking was low.